2015
DOI: 10.1055/s-0035-1560051
|View full text |Cite
|
Sign up to set email alerts
|

N,N,N-Triphenylselenylisocyanuric Acid (TPSCA): A New Versatile Reagent for α-Phenylselenenylation of Aldehydes and Ketones

Abstract: A new, versatile reagent, N,N,N-triphenylselenyl-isocyanuric acid (TPSCA) has been prepared, characterized, and used as a source of the electrophilic phenylselenyl group. This relatively stable compound was utilized for an efficient α-selenenylation reaction of aldehydes and ketones catalyzed by L-prolinamide under mild reaction conditions. The organocatalytic asymmetric α-selenenylation of an aldehyde was also studied and the reaction was found to proceed with high enantioselectivity (96% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…The current interest in the chemistry of selenium-containing compounds is mainly due to their pharmaceutical 4,5 and synthetic applications. [6][7][8] Acyl isoselenocyanates are useful intermediates for the preparation of selenium-containing heterocycles, as they are more stable and less toxic than other reagents. [9][10][11] Acyl isoselenocyanate intermediates are readily prepared by the reaction of acyl chlorides with KSeCN, a method first described by Douglas.…”
mentioning
confidence: 99%
“…The current interest in the chemistry of selenium-containing compounds is mainly due to their pharmaceutical 4,5 and synthetic applications. [6][7][8] Acyl isoselenocyanates are useful intermediates for the preparation of selenium-containing heterocycles, as they are more stable and less toxic than other reagents. [9][10][11] Acyl isoselenocyanate intermediates are readily prepared by the reaction of acyl chlorides with KSeCN, a method first described by Douglas.…”
mentioning
confidence: 99%
“…It has been reported that diorganyl dichalcogenides can be cleaved by N ‐haloimides to form corresponding organochalcogeno halides and N ‐organochalcogeno‐substituted imide derivative [29] . Then, we tested coupling reactions of 4‐methylphenyl boronic acid ( 2 a ) with phenyl selenium chloride ( 9 ) and N , N , N ‐triphenylselenylisocyanuric acid ( 10 ) under the identified reaction conditions [30] . These two reactions afforded 3 aa only in 30% and 42% yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2013 年, Lenardão 课题组 [59] 报道了在氮气保护下, [65] . 2018 年, 我们课题组 [66] 2013 年, Greaney 课题组 [68] 报道了苯硒酚与氯二氟 甲基乙酸钠在碳酸钾作用下, 于 95 ℃下, 在 DMF 中反 应 8 h, 以 65%的产率得到二氟甲硒基化产物(Scheme 32).…”
unclassified